Penerapan Digital Marketing dalam Upaya Mengembangkan UMKM Produk Teh Rosella di Kelurahan Ngipik - Rohali, Mediana Cesyanti Ajeng; Kusumasari, Indah Respati (Jurnal Bisnis Indonesia, 2024)
Currently, Small and Medium Micro Enterprises is one of the sectors in terms of the economy that ishighly noticed by the government, MSMEs in Indonesia are also very helpful to improve the country'seconomy. Digital marketing becomes an event for promoting or marketing a product because it isconsidered more effective and efficient, but many MSMEs still do not utilize it, one of which is theflagship MSMEs of Ngipik Village, namely Tea Rosella. MSMMEs Tea Rosella Ngipik Village has notutilized digital as its business medium due to the lack of human resources that take care of the MSMEsand the lack of knowledge about digital-based technologies. In this community service, the people ofNgipik Urban Village, especially business people, will be given knowledge of digital marketing tosupport their business activities. Activities are carried out using four methods, namely observation,data collection, digital marketing socialization and digital marketing activities assistance practice.The socialization activities held received good results with very good enthusiasm from the participantspresent, as well as online marketing activities were also quite good with audiences who saw posters ofrosella tea products. With a lack of public knowledge about digital business, it is hoped that there willbe assistance for business operators in Ngipik Village. Rosella tea, which is the flagship product ofKecamatan Ngipik, needs to be considered and redeveloped by increasing the available resources.Keywords: Micro Small and Medium Enterprises; Digital Marketing; Rosella